Changes in crystal structure of MWCNTs under impact of high-powered pulsed ion C:H beam - V. V. Bolotov; V. E. Kan; E. V. Knyazev (Омский научный вестник)
The structure of multi-walled carbon nanotubes exposed to a pulsed high-power ion beam is investigated using the methods of Raman spectroscopy and transmission electron microscopy. It has been shown that irradiation with an ion beam generates significant defects in the structure of nanotubes. With an increase in the number of pulses, processes associated with the annealing of defects in the internal structure of the samples are observed. Electron microscopy data make it possible to distinguish two types of defects leading to a decrease in the interlayer distance of the carbon nanotube wall.